The Rare Large Common Peroneal Nerve’s Schwannoma—A Case Report and Literature Review - Rudiansyah Harahap; Nurmaliannysa Dwinandia Harahap (Case Reports in Oncological Medicine)
Schwannoma in the popliteal fossa is still rare, often diagnosed late because it grows slowly and has no symptoms. It is often misdiagnosed with connective tissue tumors or with neurological disorders originating in the spine or disorders of the peroneal nerve. Schwannoma within the common peroneal nerve is still rare in the popliteal fossa, with most tumor sizes around 2 cm in diameter due to their smaller size of nerve but can cause neurologic disturbance, especially when it is large. And over a long time, it can cause serious complaints like neurological deficits and make surgery difficult by leaving greater sequelae. There is no data yet showing the incidence of schwannoma in the common peroneal nerve. In this case, a 36-year-old woman, for 5 years, feels soreness in the popliteal fossa and pain in the right instep, suspected that a nerve was pinched, due to an abnormality in the spine. As time went on, there was a lump in the fold of the right knee, suspected to be a Baker’s cyst. As time went by, the complaint was burning pain in the right instep to the lateral ankle and distal right lower leg, disturbing sleep. Tinel’s sign was positive. The right instep has hypoesthesia and a slight drop in the foot. On radiological examination of the right knee, a circumferential mass appeared, measuring 5 cm×4 cm. The diagnosis is suspicious for a common peroneal nerve tumor. The encapsulated operation to remove the tumor was carried out with a size measuring 5 cm×4.5 cm×4 cm. The histopathological examination showed schwannoma. After surgery, the pain disappeared, hypoesthesia and a slight drop in the foot underwent physiotherapy, and stimulation with the result gradually improved. A thorough early examination includes correct and systematic anamnesis, physical examination, and neurological evaluation such as paraesthesia, hypoesthesia, and Tinel’s sign; also, additional examinations, such as radiographic, ultrasound, and MRI, are needed for early detection of schwannoma so that delays in diagnosis and surgery can be avoided to prevent neurological deficits.